TaDIR1-2, a Wheat Ortholog of Lipid Transfer Protein AtDIR1 Contributes to Negative Regulation of Wheat Resistance against Puccinia striiformis f. sp. tritici - Ahmed, Soyed M.; Liu, Peng; Xue, Qinghe; Ji, Changan; Qi, Tuo; Guo, Jia; Guo, Jun; Kang, Zhensheng (Frontiers in Plant Science, 2017)
Very few LTPs have been shown to act through plasma membrane receptors or to be involved in the hypersensitive response (HR). DIR1, a new type of plant LTP interacts with lipids in vitro, moves to distant tissues during systemic acquired resistance (SAR) and therefore is thought to be involved in long-distance signaling during SAR. However, the exact functions of DIR1 orthologs in cereal species under biotic and abiotic stresses have not been thoroughly defined. In this study, a novel wheat ortholog of the DIR1 gene, TaDIR1-2, was isolated from Suwon11, a Chinese cultivar of wheat and functionally characterized. Phylogenetic analysis indicated that TaDIR1-2 is clustered within the nsLTP-Type II group and shows a closer relationship with DIR1 orthologs from monocots than from eudicots. TaDIR1-2 was localized in the cytoplasm and the cell membrane of wheat mesophyll protoplast. Transcription of TaDIR1-2 was detected in wheat roots, stems and leaves. TaDIR1-2 transcript was significantly induced during the compatible interaction of wheat with the stripe rust pathogen, Puccinia striiformis f. sp. tritici (Pst). Treatments with salicylic acid (SA) and low temperature significantly up-regulated the expression of TaDIR1-2. Transient overexpression of TaDIR1-2 did not induce cell death or suppress Bax-induced cell death in tobacco leaves. Knocking down the expression of TaDIR1-2 through virus-induced gene silencing increased wheat resistance to Pst accompanied by HR, increased accumulation of H2O2 and SA, increased expression of TaPR1, TaPR2, TaPAL and TaNOX, and decreased expression of two reactive oxygen species (ROS) scavenging genes TaCAT and TaSOD. Our results suggest that TaDIR1-2 acts as a negative regulator in wheat resistance to Pst by modulating ROS and/or SA-induced signaling.